2017
DOI: 10.1083/jcb.201612131
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear phosphorylated Dicer processes double-stranded RNA in response to DNA damage

Abstract: Recent work implicated human Dicer in the DNA damage response. Burger et al. show that DNA damage induces phosphorylation of Dicer and promotes DNA repair in the nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 81 publications
4
86
0
2
Order By: Relevance
“…Thus, both DDRNA biogenesis and function appear to occur locally. In agreement with this model, the presence of a phosphorylated form of DICER at DNA damage sites has been recently reported, where it mediates 53BP1 foci formation (Burger et al, 2017), (Burger and Gullerova, 2018). …”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thus, both DDRNA biogenesis and function appear to occur locally. In agreement with this model, the presence of a phosphorylated form of DICER at DNA damage sites has been recently reported, where it mediates 53BP1 foci formation (Burger et al, 2017), (Burger and Gullerova, 2018). …”
Section: Introductionsupporting
confidence: 52%
“…However, whether non-coding RNA processing occurs locally at sites of DNA damage in the nucleoplasm or in the cytoplasm of damaged cells, remained to be addressed. A debate about the possibility that RNA interference factors might be active in the nucleus, was also exacerbated by the fact that DICER has been first shown to be exclusively cytoplasmatic (Much et al, 2016) and then to be recruited to sites of DNA damage in its phosphorylated form (Burger et al, 2017), (Burger and Gullerova, 2018). …”
Section: Discussionmentioning
confidence: 99%
“…A more recent study showed that Dicer is phosphorylated at position S1016 in the platform‐PIWI/Argonaute/Zwille‐connector helix cassette upon induction of DSBs and recruited to DSB sites to facilitate DDR. Dicer deficiency leads to impaired recruitment of repair factors MDC1 and 53BP1 . This is the first report on phosphorylation‐induced nuclear localisation of Dicer in human cells.…”
Section: Dicer In Maintenance Of Genome Integritymentioning
confidence: 72%
“…In this context, nuclear accumulation is likely driven by increased phosphorylation or inhibition of dephosphorylation at Ser1712 and Ser1836. Studies in human transformed cells reveal that DICER1 phosphorylation at S1728 and S1852 is required in DNA damage response, and nuclear accumulation was driven by an additional phosphorylation at Ser1016 mediated by ATM/ATR (19). During DNA damage response, phosphorylation at Ser1016 likely delays/prevents nuclear export of Dicer1, independent of dephosphorylation at Ser1712 and Ser1836, resulting in nuclear accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these cases, phosphorylation of Dicer1 was coupled with its translocation from the cytoplasm to the nucleus (18). Burger et al (19) identified an additional serine that is phosphorylated by ATM/ ATR during DNA damage response, resulting in translocation of Dicer1 from cytoplasm to the nucleus in cultured human cells. These results suggest that phosphorylation of Dicer1 is a conserved event; however, the role of Dicer1 phosphorylation and dephosphorylation in vivo in mammals remains unknown.…”
mentioning
confidence: 99%